Location Decision-Making of Equipment Manufacturing Enterprise under Dual-Channel Purchase and Sale Mode - Wei Xu; Lina Liu; Qingshan Zhang; Peng Liu (Complexity)
Based on the current status of the development of equipment manufacturing enterprises, the main influencing factors and main evaluation indicators of the equipment manufacturing enterprises in the context of dual-channel marketing are analyzed and determined. According to the organizational layout and transaction form of equipment manufacturing enterprises, the problem of equipment manufacturing enterprise location decision-making with online channel and offline channel trading mode is divided into two categories. One is the single-plant location decision problem, and the other is the multiplant location decision problem. In the single-plant location decision problem, we have established the conceptual model and mathematical model. Based on prospect theory, we use multicriteria decision-making method to quantify and standardize the evaluation index and determine the reference value, and the priority of the scheme is determined according to the final comprehensive value. In the multiplant location decision problem, we have established the conceptual model and the logical model and established the mathematical model with the goal of minimizing the cost and time. Finally, an example is given to solve the location problem of single plant and multiple plants. The feasibility of the model is proved by the solution and verification.